120 Hospital admissions in the last year of life in patients with heart failure. (4th June 2021) - Abel, Alexandra; Samuel, Nathan; Cuthbert, Joe; Kazmi, Syed; Cleland, John; Clark, Andrew
Abstract : Introduction: In the last year of life, patients with heart failure (HF) may experience increasing symptoms and hospitalisation, but there are few data from UK populations. Whether there are differences between HF phenotypes in the pattern of admissions is not known. We explored the frequency, causes, and pattern of hospitalisation for patients with HF in the 12 months preceding death. Methods: This is a retrospective analysis of patients recruited prospectively over two decades at a community HF clinic in Kingston upon Hull, UK. Patients with HF who died before August 2020 were included. We divided the cohort into three phenotypes: i) heart failure with reduced ejection fraction (HeFREF), ii) heart failure with normal ejection fraction (HeFNEF) with N-terminal pro B-type natriuretic peptide (NTproBNP) 125-399 ng/L, and iii) HeFNEF with NTproBNP ≥400 ng/L. The primary outcome was hospital admissions in the last year of life, classified as: HF, other cardiovascular (CV), or non-cardiovascular (non-CV). The primary cause of hospital admission using ICD-10 criteria was used. Results: Among 4925 patients, the median (Q1-Q3) age at death was 81 (75-87). 38% of patients were female. There were 9127 hospital admissions. The median (Q1-Q3) number of hospitalisations per patient was 2 (1-3) and days spent in hospital in the last year of life was 12 (2-25). 83% of patients had at least one hospitalisation; 20% had at least one HF hospitalisation; 24% had at least one CV hospitalisation; 70% had at least one non-CV hospitalisation. 54% of deaths were as an in-patient. HF admissions were a minority in all phenotypes, but most common in HeFREF. In each group, at least two thirds of admissions were non-CV. 6% of the admissions in 2020 (prior to August) were for COVID-19. Hospitalisations increased in the three months prior to death ( figure 1 ). Conclusion: In the last year of life in patients with HF, most hospitalisations are for non-CV causes regardless of HF phenotype. Conflict of Interest: None